Post-truth – new old lie - Bratina, Boris (Sociološki pregled, 2022)
The idea of post-truth, although the phrase itself has its previous use, has become fashionable in the last five years and after being declared the “word of the year” in the Oxford Dictionary. The author of the paper examines the limits of theoretical fertility of this concept, placing it first in the context of truth theories, and then determining its specific theoretical weight. In the exposition of his consideration of this concept, he uses the comparative-phenomenological method and interprets its definitions in a critical-reflexive approach. Uncritical acceptance of the validity of the conceptual description of post-truth leads to the illusion that we have entered a new post-epoch that is something objective and inevitable, organized not on argumentation but on playing with other people‘s feelings. Of course, there is something in the idea of post-truth: the state of post-truth must be nothing new, if its realization did not include an exponentially developed communication technique, to which manipulative postmodern subjectivity stands as a subject a never before. On the whole, the phenomenon of post-truth belongs to a wider group of phenomena such as fake news and many others, which united together form a huge potential for falsifying the experience of reality. Finally, when the idea of post-truth according to its elements is included in a broader structure, it becomes calculable both in the history of ideas and in the interpretation of concrete events within intersubjective relations. The author believes that the path to truth, if there is truth, leads through the theoretical negation of this ideological intervention. The aim of this paper is to show that, when it comes to post-truth, it is a phenomenon that does not have its own independent existence.